Analyzing Information Disclosure in the Chinese Electricity Market - Jin, Luosong; Liu, Weidong; Wang, Xiangyang; Yu, Jing; Zhao, Panting (Frontiers in Energy Research, 2021)
The electricity generation relies heavily on fossil fuels in China, which has posed great challenges on sustainable development. In 2015, China has launched a new round of power reform, aimed primarily at sustainable development and building a competitive power market system, where information disclosure system plays an important role. This paper analyzes the effects of sensitive information disclosure and constructs different information disclosure scenarios and compares the market clearing results under different scenarios. The results show that information transparency is conducive to the promotion of market efficiency. However, some problems, especially collusion, arise and bring negative impacts to the power market inevitably. Therefore, more attention should be paid to the content and quality of data transparency to avoid manipulations in the market. The data of power system is complex and various, and thus big data application may be conducive to effective information disclosure and better market regulation. Moreover, disclosure delay will help the electricity market becomes more transparent by reducing the collusion risk. Besides, the information scope and contents, timing also should be taken into consideration. These findings may provide some references for the sustainable development of the electricity industry and have certain policy implications for the policy makers.